Trends and forecasts of the prevalence and mortality of Alzheimer’s disease and other dementias in China - Hou, Mingxuan; Yang, Ling (Frontiers in Public Health, 2025)
BackgroundAs one of the most aging populations in the world, China has experienced a continuous increase in the disease burden of Alzheimer’s Disease (AD) and other dementia (ADRD). This study aims to analyze the trends in prevalence and mortality rates of AD and related dementia in China from 1990 to 2021 and to predict the disease burden by 2040.MethodsData was extracted from the Global Burden of Disease Study 2021 (GBD 2021). Joinpoint regression was used to identify significant changes in trends, while Age–Period–Cohort (APC) models were applied to disentangle age, period, and cohort effects. Bayesian Age–Period–Cohort (BAPC) modeling was used for future projections. In addition, we conducted a risk factor analysis of AD-related mortality attributable to smoking, high body mass index (BMI), and high fasting plasma glucose (FPG).ResultsIn 2021, the age-standardized prevalence of AD and other dementia in China was 1,194 per 100,000 (95% CI: 1018–1,383), and the mortality rate was 35 per 100,000 (95% CI: 9–93). The disease burden was significantly higher in females compared to males (prevalence: females 1,559 per 100,000 vs. males 846 per 100,000). Joinpoint analysis showed a significant increase in both prevalence and mortality rates after 2019 (male APC = 2.81%, female APC = 3.76%). Risk factor analysis highlighted obesity (AAPC = 9.87%) as the leading contributor to AD mortality in China, surpassing global averages. The BAPC model predicted that by 2040, the prevalence in females would increase to 1,180 per 100,000, while the mortality rate for males would stabilize at 17.6 per 100,000. Our results indicate a substantial increase in disease burden, underscoring the urgent need for strategic interventions and resource allocation to mitigate the future impact of dementia-related conditions in China.ConclusionThe disease burden of AD and related dementia in China continues to rise, necessitating enhanced early screening, optimized healthcare resource allocation, and targeted intervention strategies for high-risk female populations.